2010
DOI: 10.1002/cjce.20273
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis of glycerol with FeCo macrocyclic complex bonded to Raney Nickel support under mild reaction conditions

Abstract: The hydrogenolysis of dilute glycerol solution to 1,2-propanediol was studied in the presence of heterogeneous catalyst (FeCoL/Raney Nickel) having a heterodinuclear FeCo macrocyclic complex ionically bonded to Raney Nickel. Studies on the stability of the complex bonded to the support were carried out at different temperature as well as the effect of solvent to confirm that it was stable up to 600 • C and 100 h of refluxing. In the hydrogenolysis of glycerol, the temperature has been varied from 165 to 220 • … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For example, it was revealed that the presence of the metallic Ni in Cu-Cr catalyst helped to increase the selectivity to 1,2-propanediol (188). Recently, Anand et al (189) described the hydrogenolysis of dilute glycerol solution to 1,2-propanediol in the presence of a heterogeneous FeCo(CH 3 C 6 H 2 (CH) 2 O(CH 2 ) 3 N 2 ) 2 /Raney Ni catalyst in which the heterodinuclear FeCo macrocyclic complex and Raney Ni species were probably bound together through ionic bonding. The conversion of glycerol and the yield of 1,2-propanediol were increased when the water content in the glycerol solution increased (189).…”
Section: Supported Cu and Ni Catalystsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, it was revealed that the presence of the metallic Ni in Cu-Cr catalyst helped to increase the selectivity to 1,2-propanediol (188). Recently, Anand et al (189) described the hydrogenolysis of dilute glycerol solution to 1,2-propanediol in the presence of a heterogeneous FeCo(CH 3 C 6 H 2 (CH) 2 O(CH 2 ) 3 N 2 ) 2 /Raney Ni catalyst in which the heterodinuclear FeCo macrocyclic complex and Raney Ni species were probably bound together through ionic bonding. The conversion of glycerol and the yield of 1,2-propanediol were increased when the water content in the glycerol solution increased (189).…”
Section: Supported Cu and Ni Catalystsmentioning
confidence: 97%
“…Recently, Anand et al (189) described the hydrogenolysis of dilute glycerol solution to 1,2-propanediol in the presence of a heterogeneous FeCo(CH 3 C 6 H 2 (CH) 2 O(CH 2 ) 3 N 2 ) 2 /Raney Ni catalyst in which the heterodinuclear FeCo macrocyclic complex and Raney Ni species were probably bound together through ionic bonding. The conversion of glycerol and the yield of 1,2-propanediol were increased when the water content in the glycerol solution increased (189). Such results were in line with the findings that low glycerol concentration was important in reducing the probability of dehydration reaction and hydrocracking (190 …”
Section: Supported Cu and Ni Catalystsmentioning
confidence: 98%
“…Two major approaches are: (i) purifying glycerol to synthetic glycerin for later applications in drug/pharmaceuticals industries (Bernesson et al, 2004; Wicke et al, 2008; Malca and Fausto, 2011). Moreover, synthetic glycerin from fossil sources is being gradually substituted by glycerol from natural sources in the market (Niederl‐Schmidinger and Narodoslawsky, 2008), and (ii) converting glycerol to high‐value chemicals via different reactions such as condensation to [1,3]dioxan‐5‐ols and [1,3]dioxolan‐4‐yl‐methanols (Deutsch et al, 2007), hydrogenolysis to propylene glycol (Dasari et al, 2005; Lechon et al, 2009; Anand et al, 2010), dehydration to acrolein (Yang et al, 2008), oxidation to glyceric acid, tartronic acid and, oxalic acid (Ketchie et al, 2007) and etherification to higher glycerol ethers used as oxygenate additives for fuels such as biodiesel and diesel petroleum (Klepacova et al, 2007; Kiatkittipong et al, 2011) or gasoline (Kiatkittipong et al, 2010). Sometimes, it is directly used as a fuel for heat generation (Soimakallio et al, 2009; Thamsiriroj and Murphy, 2010) or as animal feed in agricultural industry (Malca and Fausto, 2011).…”
Section: Introductionmentioning
confidence: 99%